(De)territorializing the home. The nuclear bomb shelter as a malleable site of passage. (August 2017) - Berger Ziauddin, Silvia
This paper explores the worldwide unprecedented bunker infrastructure of Switzerland. Since the 1960s, the country has built hundreds of thousands of nuclear bomb shelters in family homes. Drawing on poststructural theories of social practice and ritual theory, the all-pervasive structures in the private sphere are analyzed as transitory spaces that coordinate the movement and connections between different milieus, regimes, and bodies. By studying the operational scripts of the authorities and the spatial arrangements and artifacts of the shelter, the paper argues that a sequenced set of "rites of passage" were to be practiced in order to guarantee a transition into the postapocalypse without any violations of norms, social roles, and affective regimes. However, this "territorializing" process launched by the state with the aim of engineering a "bomb-proof" society met with little success. By ignoring, distorting, or violating the constant prewar situation in their homes, Swiss people, as early as in the 1970s, started to undermine the shelter as an instance of concrete governmentality. Being traversed by various processes of "deterritorialization" the bunker lost its function as a locus of secured passage and transformed into a highly dynamic "empty space" that hides, till this day, residua for creativity and difference.